Exploring diet-induced ketosis with exogenous ketone supplementation as a potential intervention in post-traumatic stress disorder: a feasibility study - Edwards, Maria G. P.; Furuholmen-Jenssen, Tobias; Søegaard, Erik Ganesh Iyer; Thapa, Suraj Bahadur; Andersen, Jens R. (Frontiers in Nutrition, 2024)
Background Post-Traumatic Stress Disorder (PTSD) is a severe and pervasive mental disorder, and patients experience numerous distressing symptoms and impairments that significantly impact their lives. In addition to being a mental disorder, PTSD is strongly associated with a wide range of metabolic abnormalities that affect the entire body. Existing treatment options of psychotherapy and medications are often ineffective. Exploring other potential treatments is necessitated. The ketogenic diet has shown potential as a metabolic therapy in certain neurological and mental disorders and is a promising intervention in the treatment of PTSD. Aim This study aimed to examine if a 4-week ketogenic diet intervention supplemented with exogenous ketones (KD-KS) was feasible in adult patients with PTSD, to what extent it was possible to recruit patients, attain and maintain ketosis (plasma concentration of β-hydroxybutyrate (BHB) ≥ 0.5 mmol/L), the occurrence of serious adverse reactions and adverse reactions to KD-KS, and acceptance of treatment. Our exploratory aims were changes in PTSD symptoms and health-related quality of life (QoL) from baseline to 4 weeks. Methods Patients 18 ≤ 65 years old, diagnosed with PTSD, and receiving outpatient treatment for PTSD at Southern Oslo District Psychiatric Centre (DPC), Oslo University Hospital, Oslo, Norway, were included. The intervention consisted of a ketogenic diet supplemented with β-hydroxybutyrate salt to obtain ketosis. PTSD symptoms were measured with the PTSD Checklist for DSM-5 (PCL-5) and QoL was measured with the RAND 36-Item Health Survey 1.0. Results During a 21-week inclusion period, three of four eligible patients (75% [95% CI: 30 to 95%]) were included. Two patients (67% [95% CI: 21 to 94%]) completed the 4-week intervention and one patient (33% [95% CI: 6 to 79%]) completed 2 weeks of intervention before discontinuing. Ketosis was achieved on day 1 in one patient, and on day 2 in two patients, and was maintained in 87% of the intervention. There were no serious adverse reactions. Adverse reactions were reported in a total of 70% of intervention days, the most frequent being headache followed by fatigue. The participant-perceived degree of adverse reactions was low to moderate. The treatment was accepted by patients on all intervention days. PCL-5 decreased by 20 points (70 to 50) in patient 1 and by 10 points (50 to 40) in patient 2, from baseline to 4 weeks, which is a reliable and clinically meaningful improvement. QoL improved in six of eight RAND-36 subscales in patient 1 and three of eight in patient 2. Patient 3 did not complete assessments after week 2. Conclusion To the best of our knowledge, this feasibility study is the first study examining a ketogenic diet intervention in patients with PTSD. Three of four predefined feasibility criteria were achieved. Ketosis was attained fast and maintained, patients were compliant and there were clinically meaningful improvements in PTSD symptoms and QoL. Despite the small sample size, the knowledge obtained in this study is important for the planning of future studies with ketogenic diet interventions in this patient group. It is a first step for potential dietary and metabolic therapies in PTSD. Further feasibility and pilot studies with larger sample sizes are needed to determine feasibility and safety before planning future randomised controlled trials investigating an effect. Clinical trial registration https://ClinicalTrials.gov, identifier NCT05415982.